REFORMULASI PENGATURAN JANGKA WAKTU PIDANA KURUNGAN SUBSIDER PIDANA DENDA DALAM TINDAK PIDANA KORUPSI - Osshy Sari Sukma; Dessy Artina; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In court judgment of corruption, there is often a lack of uniformity of court judgment regarding the term of criminal confinement in lieu of criminal fines. While the nominal criminal penalties on these court judgment are exactly the same. This certainly harms the right of the convicted person to obtain justice, legal certainty and equality before the law. The purpose of this thesis is; first, to find out the time limit for the confinement of the criminal confinement subsidiary fines in the case of corruption in positive Indonesian law. Second, to find out the reformulation of the term of criminal confinement as substitute of criminal fines in corruption cases.The type of research used in this legal research is normative juridical method, with the study of legal principles namely the principle of legal certainty. This research is descriptive in nature, which is a study that aims to make a clear and detailed picture of the problem. The data source used is secondary data. Data collection techniques in this study with a literature review method after the data collected and then analyzed to draw conclusions.From the results of research and discussion, it is known that, First, there are no definite limits regarding the term of confinement in lieu of criminal fines in cases of corruption in positive Indonesian law. The limitation regarding the period of confinement in lieu of fines is not contained in Law Number 20 of 2001 Amendment to Law Number 31 of 1999 concerning Eradication of Corruption. Limitation on the period of confinement in lieu of fines is only regulated in the Criminal Code which is a general rule. While the nominal of criminal penalties in the Criminal Code although it has been converted by PERMA Number 2 of 2012 is too smaller than the nominal of fines that are threatened in corruption cases , so it cannot be used as a guideline. Secondly, the expected reformulation is the rule regarding the period of confinement in lieu of fines in the criminal act of corruption which was only guided by the Criminal Code which is a general rule, become updated with the term of the limitation of the period of confinement for a substitute fine specifically in the Act on Eradication of Acts Criminal Corruption. In order to have clear guidelines so as to create court judgment that meet the value of justice, and legal certainty and uniformity of court judgment between convicts who are sentenced to a fine with the same nominal. The author's suggestion, First, to minimize the inconsistency of court judgement, the government must immediately update the rules regarding the period of imprisonment as a substitute for criminal imprisonment in corruption cases. Second, the renewal of the rules regarding the limit of criminal time must be carried out accompanied by synchronization of the nominal fines threatened in the Corruption Eradication Law, so that these limits can actually be used as definite guidelines.Keywords: Reformulation - criminal confinement - Criminal Fines - Corruption